PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI (STUDI PADA SATUAN KERJA PERANGKAT DAERAH PEMERINTAH PROVINSI JAWA TENGAH) - Novianti Mugi Rahayu, 16.05.62.0024; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
This research examines the effect of the competence of human resources, internal control system and organizational commitment to quality of local government financial statement with organizational commitment as moderation variable. This research was an explanatory research of Regional Work Unit (SKPD) in Central Java Provincial Government. The sampling method used purposive sampling technique. Relationship and (or) influence between variable is described by using double linear regression analysis. The result showed that the competence of human resources, internal control system and organizational commitment have positive effect and significant to quality of local government financial statement, while organizational commitment cannot as moderation variable from relationship between the competence of human resources and internal control system to quality of local government financial statement. Keyword : competence of human resource, internal control system, organizational commitment and quality of financial statement.